The Correlation between Giving Breast Feeding Site Food toward Diarhea Occurance to Infant less than Six Month in Koto Tinggi Village, the Public Health Centre of Working Area Rambah during May â June 2010 - -, ANDRIANA; -, SYAFNIAR (Jurnal Martenity and Neonatal, 2012)
Background: The priority of Indonesian health development is aimed at effort of the mortality degradation to infants and infants less than five year. In 2008, the diarhea outbreak occured in 15 provinces in Indonesia to 8.443 infants with the mortality degree 209 infats or 2.48%, increased from the year of 2007. The persentage of diarhea outbreak to infants in public health centre working area Rambah is the higest in Rokan Hulu regency with 196 occurances.